Biophilic Design and Children’s Well-Being in Kindergartens in Henan, China: A PLS-SEM Study - Huizi Deng; Raha Sulaiman; Muhammad Azzam Ismail (Buildings)
Urbanisation and reduced natural spaces pose increasing challenges to children’s holistic development in early learning environments. This study investigates how four biophilic design elements—water, plants, animals, and ecosystems—affect the physical, mental, and social well-being of kindergarten children in Henan Province, China. A quantitative questionnaire survey was conducted with children, parents, and teachers from four selected kindergartens. The questionnaire consisted of three parts: demographic information, preferences toward biophilic design elements, and perceived impacts of these elements on children’s development. Considering young children’s limited ability to self-report psychological and emotional states, children’s preferences were statistically compared to those of parents and teachers using IBM SPSS Statistics Version 26. Results showed no significant differences; thus, data from parents and teachers were retained for further analysis. Subsequently, Partial Least Squares Structural Equation Modelling (PLS-SEM) was applied to explore relationships between biophilic elements and children’s developmental outcomes. Results indicated that water and animal elements were associated with higher levels of physical activity and psychological resilience, plants were linked to greater social adaptability, and ecosystem landscapes were related to overall indicators of child development. Because the dataset is geographically limited, these quantitative results should be interpreted as exploratory evidence. Importantly, these interventions can be feasibly incorporated into existing facilities, offering practical avenues for swift implementation. To better facilitate such practical implementation, this study synthesises key findings into a comprehensive framework, explicitly outlining how these biophilic elements can be prioritised and effectively integrated into kindergarten designs. Future research is recommended to examine long-term effects and cultural adaptability.